Automatic label removal from digitized weld radiographs - Soo, Say Leong; Ratnam, Mani Maran; Samad, Zahurin; Khalid, Mohd. Ashhar (Penerbit UTM Press, 2007)
This paper presents a methodology to remove labels automatically from digitized weld radiographs as part of the automatic weld defect detection process. An algorithm was developed to detect and remove labels printed onto weld radiographs before weld extraction algorithm or defect detection algorithm is applied. Normality test was used to determine if the intensity profile parallel to the weld contains label pixels. Thresholding followed by region filling operations were carried out to remove the labels. The algorithm was tested on 50 weld radiographs with labels and the labels on 90% of these images were successfully removed.